Dari Teologi Ke Ekologi: Kontroversi Konsesi Tambang Nahdlatul Ulama dari Kacamata Teologi Lingkungan Sayyed Hossein Nasr - Rizky HK, Muhammad (UIN Mataram, 2024)
This article explores the controversy through the perspective of environmental theology developed by Sayyed Hossein Nasr. Nasr, an Islamic scientist and theologian, argued that the principles of trust (responsibility) and caliph (leader) in Islam emphasize the importance of wise and sustainable management of natural resources. He also criticized consumerism and exploitation that undermines the ecological balance and spirituality. Viewed from Nasr's point of view, this article suggests that NU's mining concessions need to be evaluated to ensure their conformity with the principles of sustainable development and environmental responsibility, as well as the need for education and awareness of environmental theology in mining practices.